2015 8th International Conference on Human System Interaction (HSI) 2015
DOI: 10.1109/hsi.2015.7170668
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the everyday use of head-worn computers

Abstract: (a) Setting up a HWC.(b) Taking a picture on the bike.(c) Recording a video on-the go.(d) Checking the weather in winter.(e) Messaging during shopping. Abstract -Early research on head-worn computers (HWCs) has focused on hardware and specific applications. However, there is little research about the everyday usage of head-worn computers in particular aspects such as: context of use, social acceptance across different activities, audiences and interaction techniques. This paper provides insights into the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The PhotoNav UI was held constant across display modalities to avoid introducing bias, yet, Vogl et al [48] concluded that interface design should be based on device and use context. Yeh et al [52] found that clutter on HMDs rendered it less effective than handhelds with similar information.…”
Section: Context Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…The PhotoNav UI was held constant across display modalities to avoid introducing bias, yet, Vogl et al [48] concluded that interface design should be based on device and use context. Yeh et al [52] found that clutter on HMDs rendered it less effective than handhelds with similar information.…”
Section: Context Of Usementioning
confidence: 99%
“…Micro-interactions should be based on screen elements that are easy to spot on the HMD, with minimal detail. A study conducted by Vogl et al [48] on everyday use of head-worn computers also suggested that HMDs should be used for micro-interactions. Further bolstering this point is an earlier study by Oulasvirta et al [33], which showed users' attention span for a mobile device is about 4-8 seconds.…”
Section: Detail Depends On Modalitymentioning
confidence: 99%